Proses Pembuatan Sprocket Adjuster Katazure RS50 B20 Menggunakan Bahan Baja Karbon S45C di PT. XYZ - Arkan Ardiansyah Ardanaputra; Kardiman (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The process of making the Katazure RS50 B20 Sprocket Adjuster using S45C carbon steel at PT. XYZ is research that explores the manufacturing processes and technology involved in the production of these components. The main raw material, S45C carbon steel, was selected to meet the strength and durability requirements required for applications in sprocket adjusters. This research covers the main stages in manufacturing, including cutting the material, forming processes, heating for hardening, and finishing to achieve dimensions and tolerances that comply with technical specifications. In addition, quality aspects such as dimensional control, hardness and material microstructure are also analyzed to ensure the final quality of the Katazure RS50 B20 Sprocket Adjuster. By using S45C carbon steel material and a controlled manufacturing process, this product is expected to provide reliable and long-lasting performance in practical applications. The results of this research are expected to provide valuable insight into the manufacturing process of complex and important machine components such as sprocket adjusters in the modern manufacturing industry